2017
DOI: 10.1039/c7np00027h
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from Isodon species: an update

Abstract: Covering: December 2005 to June 2016. Previous review: Nat. Prod. Rep., 2006, 23, 673-698Over the last decade, great efforts have been made to conduct phytochemistry research on the genus Isodon, which have led to the isolation and identification of a number of diterpenoids. At the same time, these newly reported diterpenoids with diverse structures have led to new findings on their biological functions and chemical synthesis research. In this update, we review more than 600 new diterpenoids, including their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(105 citation statements)
references
References 204 publications
1
100
0
Order By: Relevance
“…Both necrotic and apoptotic cell death are associated with Ca 2+ entry into the cells during status epilepticus. The Ca 2+ channel blockers depressed epileptic depolarizations of neurons and inhibited the spread of epilepsy [86,87]. In this study, the results of pharmacology test show that flunarizine and some of its analogs possess anticonvulsant effects thus further confirming the anticonvulsant activity of calcium channel blockers.…”
Section: No Cinnamic Acid Derivatives Pharmacological Activity Mechasupporting
confidence: 61%
See 1 more Smart Citation
“…Both necrotic and apoptotic cell death are associated with Ca 2+ entry into the cells during status epilepticus. The Ca 2+ channel blockers depressed epileptic depolarizations of neurons and inhibited the spread of epilepsy [86,87]. In this study, the results of pharmacology test show that flunarizine and some of its analogs possess anticonvulsant effects thus further confirming the anticonvulsant activity of calcium channel blockers.…”
Section: No Cinnamic Acid Derivatives Pharmacological Activity Mechasupporting
confidence: 61%
“…Our research was based both on those strategies and also on literature data mentioned above. The results of ten tested substances are quite encouraging and further modification of the structures might lead to discovering new potential anticonvulsants [85][86][87][88][89][90].…”
Section: No Cinnamic Acid Derivatives Pharmacological Activity Mechamentioning
confidence: 99%
“…Previous studies have shown that they are rich sources of diterpenoids with diverse structural scaffolds, such as ent-kauranes, entabietanes, ent-atisanes, and have a range of biological activities. [1][2][3] Isodon rubescens is a perennial herb distributed widely in Henan, Guizhou, Hebei, Jiangxi, Hubei, and some other provinces of P. R. China. 4 It has attracted great attention due to the traditional uses in folk medicine for the treatment of respiratory and gastrointestinal bacterial infections, inammation, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The ent-kaurene diterpenoids are af amily of complex, bridged, polycyclicn atural products that display many promising biological activities,i ncluding anticancer,a ntifungal, and antiviral activities. [1] According to the proposed biosynthesis,j ungermannenones are generated by the rearrangement of ent-kaurene diterpenoids through carbocationic pathways. [2] Many members of these two families,i ncluding (+ +)-jungermatrobrunin A( 1), [3f] (À)-1a,6a-diacetoxyjungermannenone C ( 2), [3f] (À)-jungermannenone C( 3), [2a] (+ +)-12hydroxy-1a,6a-diacetoxy-ent-kaura-9(11), 16-dien-15-one (4), [3f] (À)-oridonin (5), [3b] (+ +)-pterisolic acid B( 6), [3g] (À)-steviol (7), [3a] (À)-excisanin A ( 8), [3c] (+ +)-pseurata C ( 9), [3d] and (+ +)-lungshengenin D( 10), [3e] share ac ommon bicyclic [3.2.1] ring system (Figure 1).…”
mentioning
confidence: 99%
“…[2] Many members of these two families,i ncluding (+ +)-jungermatrobrunin A( 1), [3f] (À)-1a,6a-diacetoxyjungermannenone C ( 2), [3f] (À)-jungermannenone C( 3), [2a] (+ +)-12hydroxy-1a,6a-diacetoxy-ent-kaura-9(11), 16-dien-15-one (4), [3f] (À)-oridonin (5), [3b] (+ +)-pterisolic acid B( 6), [3g] (À)-steviol (7), [3a] (À)-excisanin A ( 8), [3c] (+ +)-pseurata C ( 9), [3d] and (+ +)-lungshengenin D( 10), [3e] share ac ommon bicyclic [3.2.1] ring system (Figure 1). [1] Their fascinating architectures and potential biological activities have attracted significant attention from the synthetic community for decades.Inrecent years,anumber of impressive synthetic studies have been reported based on various elegant strategies for constructing the unique bicyclic[ 3.2.1] framework. [4,5] Recently,(+ +)-jungermatrobrunin A(1)was isolated from the liverwort Jungermannia atrobrunnea together with (À)-1a,6a-diacetoxyjungermannenone C (2)and (+ +)-12-hydroxy-1a,6a-diacetoxy-ent-kaura-9(11), 16-dien-15-one (4).…”
mentioning
confidence: 99%